La no univocidad del concepto de autor desde la perspectiva de Wittgenstein y Foucault - Silva, Eduardo Graziosi [UNESP]; Martinez-Avila, Daniel [UNESP]; De Souza Gracioso, Luciana [UNESP] (My University, 2017)
Due mainly to the Information and Communication Technologies (ICT), the concept of “author” and possibilities of authorship have been broadened, regardless of the area in which the content is created. From the perspective of Wittgenstein’s “language games” and Foucault’s concept of “author,” we analyze the uses, reuses and resignifications attributed to the concept of “author” in the areas of Law, Engineering and, Library Science. We found a non-univocity of the concept based on its transformations and changes over time according to the rules and conventions of each area.
The non-univocity of the concept of “author” from the perspective of Wittgenstein and Foucault
Keywords: Author; Authorship; Foucault; Ludwig; Michel; Wittgenstein